Pancreatic Tuberculosis with Vascular Involvement and Peritoneal Dissemination in a Young Man - Meng Zhu; Ning Zhang; Wei Tao; Zhitao Wang; Shuixiang He (Case Reports in Medicine)
Pancreatic tuberculosis (TB) is an extremely rare form of extrapulmonary tuberculosis even in endemic areas that masquerades as a mass or inflammation because of lack of typical clinical manifestations and radiologic features and therefore usually misdiagnosed as a pancreatic malignancy or pancreatitis. Here we present a 23-year-old young man with pancreatic tuberculosis mimicking pancreatic head carcinoma A man who suffered from upper abdominal pain and nausea for half a month was admitted to our hospital. Narrow band imaging (NBI) and gastroscopic imaging, together with endoscopic ultrasonography (EUS), revealed a duodenal bulb mucous prominences lesion. Computed tomography (CT) and magnetic resonance imaging (MRI) both suggested a pancreatic mass which resembled a pancreatic head tumor that had a higher risk of malignancy. The patient therefore accepted an exploratory laparotomy and pancreatoduodenectomy, Whipple operation. Biopsies of pancreas, duodenum, lymph nodes, omentum, and adipose tissues were all performed, revealing tuberculosis infection in pancreas, hepatic portal vein infiltration, and peritoneal dissemination. The patient was treated successfully after operation and recovered with standard anti-TB drugs for 6 months. Timely reporting of this rare case can help physicians improve their ability to identify several specific illnesses and diseases that share confusing signs or symptoms clinically and radiographically.